The Revival of Family Waqf: A Systematic Review of Law, Governance, and Intergenerational Wealth Preservation - Muslim Marpaung; Irma Suryani Lubis (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Family waqf is a classic instrument in Islamic economics that plays a crucial role in maintaining wealth sustainability and intergenerational well-being. However, its application in the context of modern law and economics still faces various challenges, such as overlap with Islamic inheritance law (farāʾiḍ), limited regulations, and weak governance. This article aims to systematically review the academic literature on the revival of the family waqf concept in the context of contemporary Islamic law, modern governance, and its potential contribution to wealth preservation. The approach used is a Systematic Literature Review (SLR) using the PRISMA method, covering studies from 2000–2025 from various sources indexed by Scopus, DOAJ, and Google Scholar. The results of the study indicate that regulatory modernization, integration with the Islamic financial system, and the implementation of technology-based governance are key factors in reviving the role of family waqf as an instrument of social justice and economic sustainability for the community.